Development of Android-Based TINTA-QU Application for Islamic Education in Elementary School - Mulyana Abdullah; Ani Nur Aeni; Dini Sahila; Indri Deniawati; Selina Rizqiany; Ahmad Zaldi (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2025)
Objectives: This study aims to develop an interactive and engaging Android application prototype called TINTA-QU (At-Tin, Tajwid, Al-Qur’an Hadits Bersamaku) for learning purposes. Method: This study used an R&D approach with the ADDIE model. It was conducted in an elementary school in the Sumedang region with a sample of 23 fourth-grade students selected purposively. Data were collected through validation by media and subject matter experts, as well as student response questionnaires. Analysis was performed using percentage calculations to determine the feasibility of the application. Results: The results show that the TINTA-QU application is feasible for use and received positive responses from experts and students. Interactive multimedia features, tajwid content, and character-based Al-Qur'an material increase student motivation and understanding in Islamic Religious Education learning. Theoretical Contribution: The results of this study support the application of Multimedia Learning Theory in the context of technology-based Islamic Religious Education and reinforce the ADDIE model in the development of digital media based on Smart Apps Creator (SAC) as a platform for elementary school-level Qur'an learning media. Implication: This application has the potential to support independent learning and increase learning motivation. Further research is recommended to expand the scope of the material.